PENGARUH MEDIA CELENGAN TERHADAP KEMAMPUAN MENYIMPAN SISA UANG SAKU PADA SISWA TK KUNCUP MELATI SUKOLILO SUKODADI LAMONGAN - Khulsum, Umu; Suradji, Muchamad; Umroh, Ida Latifatul (MAANA: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This research is motivated by the condition of children who are not yet able to recognize the concept of money, recognize the nominal value of money, recognize the concept of saving, mention the benefits of money, recognize piggy banks and save the remaining pocket money. Thus, the aim of this research is to determine the effect of piggy bank media on children’s ability to save remaining pocket money. This research uses quantitative research using PreExperimental, namely with the One Group Pretest Posttest Design type. The sample for this research was group B children at Kuncup Melati Kindergarten, with 21 children used as samples. Data collection techniques use observation, tests and documentation. The stages in this research are pretest, treatment and posttest. The Normality Test in this study used the Shapiro - Wilk test which obtained pretest data of 0.092 and posttest of 0.71 from both data with a normal distribution. Hypothesis testing in this research uses the Paired Sample Test which is part of parametric statistical analysis because it meets the requirements that the data is normally distributed. Based on the results of the Paired Sample Test test criteria, the result was that the sig. 2 - tailed, namely 0.000 < 0.05, it can be said that Ho is rejected and Ha is accepted, so it can be interpreted that there is an influence of the piggy bank media on the ability to save remaining pocket money. Based on the results of the N-Gain Score test calculation, the percentage result was 64%, so it can be concluded that the influence of piggy bank media on children’s ability to save remaining pocket money is 64%, which is included in the medium category.